THE EFFECT OF SERVICE QUALITY ON PUBLIC SATISFACTION AT THE AMUNTAI SELATAN SUB-DISTRICT OFFICE, HULU SUNGAI UTARA REGENCY - Rina Emilyana; Hanida Hanida (PPPM STIA Amuntai, 2025)
The sub-district office is a regional government institution tasked with administering government services. At the Amuntai Selatan Sub-district Office, located in Hulu Sungai Utara Regency, the quality of public service is not yet optimal. For example, facilities and infrastructure are not yet capable of handling the maximum workload, and service satisfaction assessments are still often conducted manually using cards in a container/box. This is because the general public often receives assistance in using computers and other devices. Based on this information, this study aims to understand the influence and various important aspects of the quality of services provided to the public at the Amuntai Selatan Sub-district Office, Hulu Sungai Utara Regency. The method used in this study is a quantitative approach with a descriptive approach. The data collection method consisted of observation, documentation, and questionnaires. Approximately fifty people participated in this study, using a sampling technique through insider informants. The following metrics were used to analyze the data: normality, T, linear regression, validity and reliability, and coefficient of determination. The South Amuntai District Office's general public and public services are of varying quality, according to the study's findings. This can be seen from the results of the hypothesis test using simple linear regression, where the regression equation obtained: Y = -3.312 + 0.483X. This means that every one unit increase in variable X (Service Quality) will increase variable Y (Public Satisfaction) by 0.483. This finding indicates a positive relationship between service standards and public willingness to make payments. Finally, based on the results of the t test, the tcount value was obtained at 16.085. Meanwhile, the ttable value at degrees of freedom (df = 48) and a significance level of 5% was 1.677. Because the calculated t value is greater than the t table, the alternative hypothesis (Hₐ) is accepted and the null hypothesis (H₀) is rejected. These findings indicate a significant difference between service quality and public response in general. In addition, the results of the correlation analysis produced an R value of 0.918, which indicates a very strong relationship between the two variables. Service quality accounts for 84.4% of the fluctuation in public opinion, according to the coefficient of determination (R2) value of 84.4%. Meanwhile, the rest is affected by other factors that were not considered in this study. This leads to the conclusion that, in the South Amuntai District government agency, which is situated in the North Hulu Sungai Regency administrative area, service quality significantly and favorably affects the community. To improve the quality of service at the South Amuntai District Office, it is recommended that the Sub-district Head pay more attention to employee discipline by controlling employee attendance and work, increasing work supervision, strict sanctions, improving infrastructure, and providing regular technical guidance. All employees are advised to be disciplined in terms of time, be responsive in receiving complaints, and strive to improve their understanding of computer use. The community is also advised to participate in monitoring services by providing criticism and suggestions in the suggestion box provided by the sub-district